Identification And Characterization Of Fusarium Species From Paddy, Sugarcane And Maize - Heng , Mei Hsuan (2010)
Most of the plant pathogenic Fusarium spp. associated with paddy, sugarcane and maize are members of section Liseola or Gibberella fujikuroi species complex which mostly could not be identified or characterized accurately by only using one approach. Hence, morphological, mating studies and molecular analysis were applied in this study to identify, characterize and to observe the genetic variability of Fusarium spp. from three hosts, paddy, sugarcane and maize. A total of 86 isolates of Fusarium were used in the present study which comprised 36 isolates successfully isolated from diseased paddy, sugarcane and maize and 50 isolates from paddy and sugarcane from the stock culture. Six species of Fusarium namely, F. fujikuroi, F. oxysporum, F. proliferatum, F. sacchari, F. subglutinans and F. verticillioides were identified by using morphological characteristics.